Training and implementation of a web-based data collection system to improve data processing - Zaid Romegar Mair; Rudi Heriansyah; Doly Nofiansyah; Muhamad Tedy Setyady (University of Merdeka Malang, 2025)
The member data collection process at the Institution for the Development and Empowerment of Women Heads of Household (PEKKA) of the Masjid Agung Palembang Foundation is still done manually using books and Excel. This causes difficulties in finding data, inaccurate data, and data may be lost. The purpose of this community service activity is to conduct socialization and training on the system that has been built, which can be accessed via the Internet. The target of the activity is the administrative section of the institution which has data over than 190 members. The system development uses a waterfall approach and discussions about the system that will be used later with a development method, which consists of planning, system design, implementation, evaluation, and ends with training. Laragon is used as a local server in system development until hosting in its publication. The web-based system developed successfully addressed previous issues by speeding up data retrieval, making updates easier, and reducing the likelihood of data loss. After the system is published, the next step is socialization and training to facilitate users and website administrators in member data collection, so that data-related needs can be met well, and innovation can be realized by transitioning from manual to digital. Based on the results of the tests conducted, the average value obtained was 4.67 out of 5, which indicates that respondents were able to use the system effectively.